2022
DOI: 10.5005/jp-journals-10084-13139
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practice Regarding Plotting of Partograph in Staff Nurses in Order to Develop and Administer a Need Based on the Job Training Program

Abstract: A partograph is one of the important tools to monitor the progress of labor and is also helpful for managing labor. Therefore, it should be used for all women during the first stage of labor admitted to a labor room. Partograph is needed for observations of the mother and fetus and also assists in early decision-making in the intranatal period, such as transfer, augmentation, and termination of labor. Aim of the study:The study was aimed to assess the knowledge and practice regarding the plotting of partograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In terms of educational qualification, the preponderance of nurses (72.9%) possessed a General Nursing and Midwifery (GNM) qualification, mirroring the findings of a recent inquiry conducted by distinguished researchers Soyam, Rawat, Anil, and Kumari (2022). In their study, a similar majority (73.33%) of nurses held GNM credentials as their educational background [3] .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In terms of educational qualification, the preponderance of nurses (72.9%) possessed a General Nursing and Midwifery (GNM) qualification, mirroring the findings of a recent inquiry conducted by distinguished researchers Soyam, Rawat, Anil, and Kumari (2022). In their study, a similar majority (73.33%) of nurses held GNM credentials as their educational background [3] .…”
Section: Discussionmentioning
confidence: 80%
“…In the present study,47.9% of the nurses were in the age of 31 to 40 years. However, an influential study conducted by Soyam D, Rawat V, Anil K P, and Kumari P (2022) asserted that the preponderance of participants (63.33%; n = 19) lie within the youthful range of 20 to 30 years old [3] . The current study revealed that a majority of the participants, 43 (89.6%) were females.…”
Section: Discussionmentioning
confidence: 99%